Activation of Toll-Like Receptor 7 Signaling Pathway in Primary Sjögren's Syndrome-Associated Thrombocytopenia - Zhang, Shuo; Qu, Jingge; Wang, Li; Li, Mengtao; Xu, Dong; Zhao, Yan; Zhang, Fengchun; Zeng, Xiaofeng (Frontiers in Immunology, 2021)
Objectives. To identify the importance of the Toll-like receptor (TLR) pathway using B cell high-throughput sequencing and to explore the participation of the TLR7 signaling pathway in primary Sjogren’s syndrome (pSS)-associated thrombocytopenia in patient and mouse models. Methods. High-throughput gene sequencing and bioinformatic analyses were performed for 9 patients: 3 patients with pSS and normal platelet counts, 3 patients with pSS-associated thrombocytopenia, and 3 healthy controls. Twenty-four patients with pSS were recruited for validation. Twenty-four non-obese diabetic (NOD) mice were divided into the TLR7 pathway inhibition (CA-4948), activation (Resiquimod), and control groups. Serum, peripheral blood, bone marrow, and submandibular glands were collected for thrombocytopenia and TLR7 pathway analysis. Results. Seven hub genes enriched in the TLR pathway were identified. Compared to that in control patients, the expression of interleukin (IL)-8 and TLR7 pathway molecules in B-cells was higher in patients with pSS-associated thrombocytopenia. Platelet counts exhibited a negative correlation with serum IL-1β and IL-8 levels. In NOD mice, CA-4948/Resiquimod treatment induced the downregulation/upregulation of the TLR7 pathway, leading to consistent elevation/reduction of platelet counts. Megakaryocyte counts in the bone marrow showed an increasing trend in the Resiquimod group, with more naked nuclei. The levels of IL-1β and IL-8 in the serum and submandibular gland tissue increased in the Resiquimod group compared with that in CA-4948 and control groups. Conclusion. pSS-associated thrombocytopenia may be a subset of the systemic inflammatory state as the TLR7 signaling pathway was upregulated in B cells of patients with pSS-associated thrombocytopenia, and activation of the TLR7 pathway led to a thrombocytopenia phenotype in NOD mice.